Quantitative Proteomic Analysis Reveals the Sites Related to Acetylation and Mechanism of ACY-1215 in Acute Liver Failure Mice - Zhang, Wen-bin; Zhang, Hai-yue; Wang, Yao; Jiao, Fang-zhou; Wang, Lu-wen; Gong, Zuo-jiong (Frontiers in Pharmacology, 2019)
Background: ACY-1215 is a well-known selective histone deacetylase 6 (HDAC6) inhibitor, and it has been considered as a potential therapeutic drug in inflammatory diseases, including acute liver failure (ALF). However, little is known about the impact of ACY-1215 treatment on histone lysine acetylation and proteome in ALF. In this study, we aim to investigate whether ACY-1215 has inhibitory effects and mechanism on the necrosis of hepatocytes; moreover, the impact of ACY-1215 treatment on histone lysine acetylation still needs further elucidation. Methods: Male C57/BL6 mice were divided into normal, model, and ACY-1215 groups. ACY-1215 (25 mg/kg) and same amounts of saline were injected intraperitoneally to the mice before the establishment of ALF model induced by lipopolysaccharide (LPS) (100 µg/kg) combined with D-gal (400 mg/kg). All animals were sacrificed after 24 h. In this study, detection programs, including quantitative proteomic analysis, transmission electron microscopy (TEM) micrographs, pathological staining, protein expression, the detection of reactive oxygen species (ROS) as well as glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) measurement. Results: The function of liver and the necrosis of hepatocytes in ALF mice were significantly normalized by ACY-1215 pretreatment. The quantitative proteomic analysis revealed that ACY-1215-restrained oxidative phosphorylation normalized the function respiratory electron-transport chain in the mitochondria. Moreover, pretreatment of ACY-1215 not only normalized the structure of mitochondria but also inhibited the generation of reactive oxygen species (ROS). Conclusions: ACY-1215 was able to inhibit necrosis of hepatocytes in ALF mice through regulating the mitochondrial-mediated oxidative stress, and we identified the common sites related to acetylation level.